2021
DOI: 10.3390/cancers13246201
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Vascular Tumors of the Head and Neck—Which Type of Therapy Works Best?

Abstract: Malignant vascular tumors of the head and neck are rare neoplasms with variable clinical presentation, wide age distribution, and variable clinical courses. The heterogeneous presentation of angiosarcomas and epithelioid hemangioendothelioma often leads to misdiagnosis and unsuitable treatment. While risk factors for angiosarcomas are previous radiation, chronic lymphedema, and exposure to arsenic, thorium oxide, or vinyl chloride, there are only limited and retrospective data available on prognostic factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 104 publications
0
2
1
2
Order By: Relevance
“…Although there was no straightforward explanation, previous literature provided evidence that Pr might lead to significant DNA genetic damage to Sprague-Dawley rats at a certain concentration ( 42 ). As for Th and Y, contrary to our results, previous studies have reported that these elements could cause genetic damage and induce cancer ( 42 45 ). However, as radiometal carriers, Th and Y exerted a beneficial action against the carcinoma of head and neck in clinical practice ( 46 , 47 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Although there was no straightforward explanation, previous literature provided evidence that Pr might lead to significant DNA genetic damage to Sprague-Dawley rats at a certain concentration ( 42 ). As for Th and Y, contrary to our results, previous studies have reported that these elements could cause genetic damage and induce cancer ( 42 45 ). However, as radiometal carriers, Th and Y exerted a beneficial action against the carcinoma of head and neck in clinical practice ( 46 , 47 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Primary angiosarcoma: Clear surgical margins correlate with better outcomes [ 65 ] and positive margins to poorer prognosis [ 66 ], which is why positive margins should always be managed by re-resection. Surgery can be challenging due to the close relation to anatomically important structures in the head and neck region [ 67 ]; however, pAS is treated by radical surgery—followed by RT [ 38 , 68 ].…”
Section: Treatment Algorithms and Strategiesmentioning
confidence: 99%
“…Mit der Kombination aus Chemo-und Lokaltherapie werden sehr gute, ereignisfreie Überlebensraten von Patient*innen mit primär lokalisierten Rhabdomyosarkomen erreicht [20,21]. Eine primäre Tumorresektion wird heutzutage nur noch dann angestrebt, wenn eine "onkologische radikale Tumorresektion ohne Verstümmelung zumindest sehr wahrscheinlich erscheint".…”
Section: Orbita Und Gesichtsschädelunclassified
“…Angiosarkome der Orbita-und Gesichtsregion (aber auch insgesamt im Kopf-Hals-Bereich) haben bekanntermaßen eine extrem schlechte Prognose, auch im Vergleich zu den anderen Weichgewebesarkomen [21]. In einer retrospektiven Analyse von Willers et al [22] liegen Überlebensrate, lokoregionale Kontrolle und Freiheit von Fernmetastasen bei 31 %, 24 % und 42 % nach 5 Jahren (im Vergleich die anderen Weichgewebesarkome: 74 %, 69 %, 83 %).…”
Section: Angiosarkomeunclassified